Pendampingan Company Visit Mahasiswa ke Kantor Akuntan Publik PKF Hadiwinata & Partners Jakarta - Ahmad Basid Hasibuan; Agustina Indriani; Atik Isniawati; Radina Modjaningrat; Saminem Saminem (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2026)
essential for fostering the motivation to enhance their professional competencies. The primary objective of these visits is to bridge the gap between classroom theory and its practical application within the business and industrial sectors. Through these visits, students are expected to gain insights into fundamental concepts, business processes, governance structures, work cultures, and operational regulations. For universities, the business and industrial sectors represent key partners in supporting the "Tridharma" (Three Pillars) of Higher Education, and company visits can be viewed as mutually beneficial, long-term initiatives. Consequently, these visits should be formalised through cooperation agreements or Memoranda of Understanding (MoUs). Furthermore, company visits provide an opportunity for universities to update their curricula—particularly in subjects such as auditing and financial accounting—thereby aligning educational content with the workforce requirements of the business and industrial sectors, such as public accounting firms. Finally, these visits can pave the way for other student opportunities, including field practicums and internship.